2019
DOI: 10.3390/ijms20236070
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Methylome and Transcriptome Analysis between the CMS-D2 Line ZBA and Its Maintainer Line ZB in Upland Cotton

Abstract: DNA methylation is an important epigenetic modification involved in multiple biological processes. Altered methylation patterns have been reported to be associated with male sterility in some plants, but their role in cotton cytoplasmic male sterility (CMS) remains unclear. Here, integrated methylome and transcriptome analyses were conducted between the CMS-D2 line ZBA and its near-isogenic maintainer line ZB in upland cotton. More methylated cytosine sites (mCs) and higher methylation levels (MLs) were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 101 publications
(150 reference statements)
1
10
0
1
Order By: Relevance
“…Furthermore, in line with decreased growth and migration in vitro, cells with suppressed CD73 expression formed significantly smaller tumors and less lung metastases than control cells 13 , 15 , 17 . Similar effects on lung metastases have also been described by other investigators 16 , 40 . Interestingly, we did not detect a significant difference in liver metastases, suggesting that CD73 may mediate specifically lung metastases.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, in line with decreased growth and migration in vitro, cells with suppressed CD73 expression formed significantly smaller tumors and less lung metastases than control cells 13 , 15 , 17 . Similar effects on lung metastases have also been described by other investigators 16 , 40 . Interestingly, we did not detect a significant difference in liver metastases, suggesting that CD73 may mediate specifically lung metastases.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, several studies have demonstrated that CD73 has prognostic value in TNBC 13 15 . No such correlation was detected among HER2+ or luminal breast cancer subtypes 15 , 16 . CD73-associated poor outcome in TNBC may stem from immune evasion, as adenosine may protect cancer cells from adaptive anti-tumor immune responses 17 19 .…”
Section: Introductionmentioning
confidence: 86%
“…Many studies have been carried out to identify genes that are differentially expressed, however paucity of the causes of the differential expression, hints us towards epigenetic regulations and transcription factors as the probable cause. Very few methylation studies have been carried out in cotton for fiber quality [79], male sterility [80], cold stress [81], salt tolerance [82], fruiting branch development [83]. Thus, there is huge scope for studies like differential methylation, studies on transcription factor, and correlating them with the differential expression patterns.…”
Section: Transcriptome Studies In Cottonmentioning
confidence: 99%
“…Reverse transcription was conducted using the PrimeScriptTM RT Reagent Kit (TaKaRa, Beijing, China). TransStartTopGreen qPCRSuperMix (Trans gen, Beijing, China) was used according to the manufacturer's instructions to conduct qRT-PCR of the genes.The internal control gene used for qRT-PCR was the cottonHis3 gene (i.e., histone 3) with primers of GhHIS3F and GhHIS3R, and relative gene expression levels were calculated using the 2-△△CT method [91],as described in detail in previous studies [92][93][94]. Each gene in each sample was analyzed with three replicates and two technical replicates.…”
Section: Real-time Quantitative Pcr (Qrt-pcr) Analysismentioning
confidence: 99%